An examination of lexical choices in Slovene translations of British and American drama - Hribar, Darja Darinka (ELOPE (Ljubljana), 2005)
The article examines lexical choices preferred by a noted Slovene translator of dramatic texts. It is based on the assumption that in spite of the fact that lexical choices offer much greater freedom in translation than, for instance, grammatical choices, they are subject to a number of intratextual and extratextual factors defining the genre, the kind of translation, and specific features of individual plays. Although examples are taken from only one set of translations of Tennessee Williams's A Streetcar Named Desire, they also refer to other working and published versions of dramatranslations into Slovene, including Albee's Whos Afraid of Virginia Woolf?, Miller's Death of a Salesman, Pinter's plays, and Shaw's Pygmalion. The shifts considered in the article relate to register, i. e. factors of language variation affecting lexical choices related to the field, mode, and tenor of discourse.
Keywords: ameriška književnost; angleška književnost; leksika; leposlovje; prevajalstvo; prevajanje; vaje